1995
DOI: 10.1093/carcin/16.3.531
|View full text |Cite
|
Sign up to set email alerts
|

Two types of normal human breast epithelial cells derived from reduction mammoplasty: phenotypic characterization and response to SV40 transfection

Abstract: A culture method to grow two morphologically distinguishable normal human breast epithelial cell types derived from reduction mammoplasty has been developed. Type I cells were characterized by a more variable cell shape, smooth cell colony boundaries, the expression of epithelial membrane antigen (EMA) and keratin 18 and the non-expression of keratin 14 and alpha 6 integrin. In addition, the Type I cells were growth stimulated by fetal bovine serum (FBS) and were deficient in gap junctional intercellular commu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
195
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 142 publications
(203 citation statements)
references
References 0 publications
8
195
0
Order By: Relevance
“…Specifically, Petersen and colleagues showed that clonal culture of luminal epithelial cells in the presence of cAMP-elevating cholera toxin resulted in the focal conversion of luminal epithelial cells into basal-like cells (Petersen and van Deurs 1988). This finding was confirmed and elaborated in a series of independent studies, and it was interpreted as evidence for stem cell activity (Kao et al 1995;Huper and Marks 2007). That cells converted by cAMP treatment indeed represent cells of the basal lineage was shown by immunomagnetical sorting of the cells based on surface markers and proteomics studies (Péchoux et al 1999).…”
Section: The Identity Of Breast Epithelial Stem Cellsmentioning
confidence: 88%
“…Specifically, Petersen and colleagues showed that clonal culture of luminal epithelial cells in the presence of cAMP-elevating cholera toxin resulted in the focal conversion of luminal epithelial cells into basal-like cells (Petersen and van Deurs 1988). This finding was confirmed and elaborated in a series of independent studies, and it was interpreted as evidence for stem cell activity (Kao et al 1995;Huper and Marks 2007). That cells converted by cAMP treatment indeed represent cells of the basal lineage was shown by immunomagnetical sorting of the cells based on surface markers and proteomics studies (Péchoux et al 1999).…”
Section: The Identity Of Breast Epithelial Stem Cellsmentioning
confidence: 88%
“…Type I cells express luminal epithelial markers and stem cell characteristics by being able to both differentiate into other cell types and to form budding structures on reconstituted basement membrane (rBM). Type II cells exhibit a myoepithelial phenotype and form spherical organoids in rBM (38). Interestingly, only type I cells could convert to type II cells not type II to type I (38).…”
Section: The Origin Of Myoepithelial Progenitor Cellsmentioning
confidence: 97%
“…Type II cells exhibit a myoepithelial phenotype and form spherical organoids in rBM (38). Interestingly, only type I cells could convert to type II cells not type II to type I (38). Thus it seems reasonable to conclude that the luminal epithelial and myoepithelial cell lineages are related, and that luminal epithelial cells give rise to myoepithelial cells, at least in the adult gland.…”
Section: The Origin Of Myoepithelial Progenitor Cellsmentioning
confidence: 98%
“…19 20 The high proliferative capacity of these cells, together with this uncommitted differentiation state, has led many observers to regard them as being derived from a small "stem cell" pool present in the basal layer of the normal gland. 21 In contrast, most normal breast epithelial cells present in the intact gland and in early passage mammoplasty cultures express CK8, CK18 (weakly), and CK19, but not vimentin. 20 "It is now accepted that the inactivation of the p53 gene, as a result of mutation, is a key step in neoplastic transformation and progression" Although several studies have investigated the expression of CKs and vimentin, EGFR, ER, and the progesterone receptor (PgR) in breast cancer, 17 18 22-30 to our knowledge, no study has directly compared p53 mutations with these phenotypic and differentiation markers in the same case.…”
mentioning
confidence: 94%